Managing Romanian Wheat Price Volatility Using Euronext Futures - Dinica (Balea), Erica Cristina; Dinica, Mihai Cristian (International Journal of Economic Practices and Theories, 2015)
The agricultural market is one of the most important markets of an economy as it affects not just the companies acting as buyers or sellers, but the entire population. Being influenced by several factors, the agricultural prices are characterized by a high volatility, the need for hedging arising. The paper analyzes the effectiveness of hedging Romanian wheat through futures contracts traded on Euronext Paris exchange. The optimal hedge ratio is estimated through several methods: the OLS regression and the error-correction model provide static hedge ratios, while the rolling windows OLS and the GARCH model provide hedge ratios that vary through time. A comparison based on the hedging effectiveness is then realised, the results showing that the time varying hedge ratios perform better than their static counterparts.